The evidence and feasibility of using pulse oximetry for the management of childhood pneumonia in low- and middle-income countries: a clinical review - Morikawa, Masahiro J.; Ganesh, Prakash R. (International Journal Of Community Medicine And Public Health, 2021)
The use of pulse oximetry (POx) for the diagnosis and management of childhood pneumonia has been of interest in recent years. In order to effectively employ POx to manage childhood pneumonia in LMICs, we aim to answer the following five questions through a literature review. These five questions are: 1) Which clinical signs are reliable to detect hypoxia? 2) What is the prevalence of hypoxia among those diagnosed with pneumonia? 3) Does the detection of hypoxia among clinical pneumonia patients improve survival? 4) How reliable are current POx devices in the field? and 5) What are the problems in introducing POx in the field? We searched three keywords-IMCI, childhood pneumonia and pulse oximetry, with the PubMed search engine and extracted 119 articles and book chapters. Each article was reviewed to answer above five questions. The literature review indicates that none of the clinical signs reliably detect hypoxia in children. The prevalence of hypoxia among pneumonia varied based on the study. 17-32% of patients without a diagnosis of pneumonia presented with hypoxia. There are currently no randomized trials available to demonstrate the benefit of pulse oximetry in childhood pneumonia survival. Various devices and probes are used in different studies and there are still technical and logistical issues related to POx device use in the field to manage childhood pneumonia in LMICs. There are numerous barriers to train healthcare workers in all levels. We need affordable, reliable, easy to use pulse oximetry for childhood pneumonia management.